Meteorological and Streamflow Droughts: Characteristics, Trends, and Propagation in the Milwaukee River Basin. Issue 3 (3rd July 2018) - Choi, Woonsup; Byun, Hi-Ryong; Cassardo, Claudio; Choi, Jinmu
Abstract : This study examined meteorological and streamflow droughts for the period from 1951 to 2006 using the Milwaukee River basin in Wisconsin as the study area in an effort to improve the understanding of drought propagation. Specifically, this study aimed to answer the following research questions: (1) What are the temporal trends of meteorological and streamflow droughts identified by drought indicators? (2) How do the drought indicators manifest drought propagation? Meteorological droughts were identified using the Effective Drought Index (EDI), and streamflow droughts were identified using a threshold-level approach. The intensity and duration of both types of drought were found to have decreased over time, most likely due to increasing precipitation. Therefore, in the study area, and likely in the larger region, drought has become of less concern. The propagation of meteorological drought into streamflow drought was detected generally after moderate and severe sequences of negative EDI that eventually led to extreme meteorological drought events. The study finds that both EDI and the threshold-level approach are effective in diagnosing meteorological and streamflow drought events of all durations.